Digital Humanities and the Decolonization of Knowledge in Nigeria: Media Studies, Postcolonial Theory, and African Epistemologies - Adekunle Ayodeji Ogunwola; Ibrahim Suberu (MD Research Center, 2026)
The rapid expansion of digital technologies has fundamentally transformed media ecosystems, knowledge production, and cultural authority across the Global South, yet existing scholarship on Digital Humanities (DH) has largely been framed through Western-centric perspectives that obscure epistemic diversity and local practices. This study aims to examine how DH reconfigures knowledge production in Nigeria by analyzing the intersection of digital media, postcolonial theory, and African epistemological traditions. Employing a qualitative literature-based approach with thematic analysis of scholarly works, policy reports, and theoretical texts on DH, media studies, and decolonization, the study synthesizes sources to construct an integrative framework. The findings reveal three key insights: first, DH expands knowledge production through digitization, computational analysis, and digital archives; second, it redistributes authority through transparency, participation, and open scholarship; and third, it democratizes distribution through open access and interoperable infrastructures. The study concludes that African philosophical frameworks, particularly Omoluabi and Ubuntu, provide crucial resources for developing culturally grounded DH approaches that resist digital colonialism. By extending DH scholarship beyond Euro-American contexts, this study contributes to contemporary debates in media and cultural studies on epistemic pluralism, digital sovereignty, and the decolonization of knowledge in an interconnected Global South.